Comparative Study of Input Shaping with Different Polarities and Modes Selection in Hybrid Control Schemes of a DPTOC System - Mohd Zaidi, Mohd Tumari; Muhammad Salihin, Saealal; Kamarul Hawari, Ghazali; Mohd Riduwan, Ghazali (Medwell Journals, 2012)
This paper presents a comparative assessment on input shaping techniques with different polarities and sways frequency modes in hybrid control schemes of a double-pendulum-type overhead crane (DPTOC) system. The hybrid control schemes consist of cart position trajectory tracking and sway control of a DPTOC system. A nonlinear DPTOC system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. The proposed method, known as the Single Input Fuzzy Logic Controller (SIFLC), reduces the conventional two-input FLC (CFLC) to a single input single output (SISO) controller. The SIFLC is developed for position control of cart movement. This is then extended to incorporate positive and negative input shaping schemes for both hook and load sway angle suppression. Both positive and negative input shaping with different modes selection is designed based on the properties of the system. The results of the response with the controllers are presented in time and frequency domains. The performances of control schemes are examined in terms of level of input tracking capability, sway angle reduction and time response specifications in comparison to SIFLC controller. Finally, a comparative assessment of the control techniques is discussed and presented.